Oral health impact profile to bilingual Pilipino - Yanga-Mabunga, S.
This thesis study compares the social impact of oral diseases and disorders among Australian and Filipino workers which provides and opportunity to translate the Oral Health Impact Profile to the Bilingual Pilipino. The methodology used is presented below. The translation of the English OHIP to Pilipino also provides for an opportunity to introduce a new oral health measure to the Philippines.
Keywords: Back translation; Oral Health Impact Profile (OHIP).